2007
DOI: 10.1002/ijc.22897
|View full text |Cite
|
Sign up to set email alerts
|

The growth inhibitory effect of actein on human breast cancer cells is associated with activation of stress response pathways

Abstract: Previous studies indicate that the triterpene glycoside actein from the herb black cohosh inhibits growth of human breast cancer cells. This study seeks to identify genes altered in human breast cancer cells by treatment with actein, using gene expression analysis. We treated MDA-MB-453 human breast cancer cells with actein at 2 doses, 20 or 40 lg/mL, for 6 or 24 hr. We identified 5 genes that were activated after each of the treatments that are known to play a role in cellular responses to diverse stresses, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…For a gene to be included in this study it must have passed set criteria for differential expression in at least 1 time point in comparisons between experimental and GAL4-only control embryos. Recent studies of gene expression using LIMMA have used the empirical Bayesian Log of Odds of differential expression factor (B) to identify differentially expressed genes (39,40). In our analysis we compared several different statistical approaches and found that using GC-RMA with LIMMA and thresholds of B Ͼ 0 and fold changes Ͼ1.5 to determine differential expression most enriched for known targets of Notch and Ras (data not shown).…”
Section: Methodsmentioning
confidence: 96%
“…For a gene to be included in this study it must have passed set criteria for differential expression in at least 1 time point in comparisons between experimental and GAL4-only control embryos. Recent studies of gene expression using LIMMA have used the empirical Bayesian Log of Odds of differential expression factor (B) to identify differentially expressed genes (39,40). In our analysis we compared several different statistical approaches and found that using GC-RMA with LIMMA and thresholds of B Ͼ 0 and fold changes Ͼ1.5 to determine differential expression most enriched for known targets of Notch and Ras (data not shown).…”
Section: Methodsmentioning
confidence: 96%
“…Oral administration of iCR or E2 for 1 week to ovariectomized rats was able to restore neuronal excitability leading to functional recovery of hypothalamic activity [14,24]. Furthermore, iCR has been shown to upregulate genes related to cell survival under metabolic stress such as hypoxia [28][29][30]. In hypoestrogenic women, the cerebral blood flow has been shown to be reduced with regional patterns resembling those of patients with mild to moderate Alzheimer's disease [31].…”
Section: Discussionmentioning
confidence: 99%
“…23 Suppressed tumor growth was also observed for other saponins like 51,52 and several other saponins. 52,53,[70][71][72][73][74][75][76][77][78][79] A further prominent feature of saponins is their antimicrobial activity. Diosgenyl 2-amino-2-deoxy-beta-D-glucopyranoside was medically active against Staphylococcus aureus and Enterococcus faecalis in a wound model simulating surgical site infections in BALB/c mice.…”
Section: Efficacy Of Saponins and Clinical Potentialmentioning
confidence: 99%